Umbilical Vascular Thromboembolism: High-Risk Factors, Diagnosis, Management, and Pregnancy Outcomes: A Scoping Review - Zhan J; Wang D; Luo C; Bi H (Dove Medical Press, 2024)
Jun Zhan,1,2 Dingding Wang,1,2 Chuanxiang Luo,3 Haiyan Bi4 1Department of Obstetrics and Gynecology, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, Sichuan, People's Republic of China; 3Department of Clinical Medicine, Medical College, Qingdao University, Qingdao, People's Republic of China; 4Office for Medical and Health Service, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of ChinaCorrespondence: Haiyan Bi, Office for Medical and Health Service, West China Second University Hospital, Sichuan University, Email 649927649@qq.comAbstract: Umbilical vascular thromboembolism is a rare condition that can lead to serious consequences such as fetal hypoxia, fetal growth restriction, and even stillbirth. However, there is currently a lack of research on the pathology, pathogenesis, clinical management, and prognosis of this condition. Therefore, the purpose of this article is to analyze this condition's high-risk factors, clinical characteristics, pregnancy management, and discuss its corresponding pregnancy outcomes. Databases such as PubMed are searched using the relevant keywords of umbilical vascular thromboembolism in worldwide. And related information is analyzed such as maternal risk factors, fetal risk factors, umbilical cord and placental risk factors, and pregnancy outcomes. The literature search yields 113 articles, 64 of which meet the inclusion criteria for umbilical vascular thromboembolism. There are 4 retrospective cohort studies and 8 case series, the rest are all case reports. A total of 262 cases of umbilical vascular thromboembolism are found. The most common maternal complications and fetal related risk factors are diabetes (25 cases, 9.5%) and stillbirths (106 cases, 40.5%), respectively. Among these 262 cases, 98 (37.4%) cases are found by prenatal ultrasound to have umbilical vascular thromboembolism and the fetus is in a viable state with complete clinical information. In addition, considering the effectiveness and safety of low molecular weight heparin in thromboembolic conditions, twenty-four patients of umbilical artery thromboembolism attempted to use low molecular weight heparin during observation. Maternal diabetes was the highest risk factor for this condition. When umbilical artery thromboembolism occurs, the incidence of stillbirth increases. Premature patients with this condition can continue their pregnancy under close external monitoring. However, due to the small sample size, further research is needed.Keywords: umbilical vascular thromboembolism, umbilical vein thromboembolism, umbilical artery thromboembolism, fetal growth restriction, umbilical vein varix, low molecular weight heparin